Effect of Mesh Wettability Modification on Atmospheric and Industrial Fog Harvesting - Kang, Jong Hoon; Lee, Jeong-Won; Kim, Ji Yeon; Moon, Jong Woon; Jang, Hyeon Seo; Jung, Sung Yong (Frontiers in Physics, 2021)
Freshwater shortage has been receiving considerable attention, and water harvesting is one of the potential solutions to this water crisis. Several researchers have tried to improve the harvesting capabilities by changing the mesh wettability for atmospheric fog harvesting. However, the wettability effect on water harvesting from white plumes has not yet been investigated thoroughly, despite industrial cooling towers being considered alternative water resources, because of the large amounts of fog plumes generated. In this study, surface wettability was modified with a robust and simple method for practical scaled up applications and we explore the influence of mesh wettability on atmospheric and industrial fog harvesting. In atmospheric fog harvesting, both superhydrophilic and superhydrophobic meshes are found to improve the harvesting performance, with the superhydrophobic treatments providing the best collection efficiency. In contrast, only superhydrophilicity improves the performance in industrial fog harvesting with flat mesh screens. We believe that this research will be useful for mesh design, as it clarifies the influence of mesh wettability on the water collection performance in both atmospheric and industrial water harvesting.